Samopoczucie w szkole uczniów ze specjalnymi potrzebami edukacyjnymi w młodszym wieku szkolnym = School wellbeing of early school-age pupils with special educational needs - Nowicka, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents a part of a larger study on the school situation of pupils with special educational needs at an earlier school age, relating to their well-being in the school environment. The aim of the study was to answer the following research questions: What is the emotional attitude towards school declared by the SEN pupils participating in the research? Do they like to return to school after longer breaks (summer holidays, winter holidays)? Would the SEN pupils surveyed like to transfer to another school and if so, for what reason? What is the image of school that they have formed in their minds? Does the SEN type differentiate the well-being at school of the pupils participating in the study?
Keywords: wellbeing; school; pupil; special educational needs; samopoczucie; uczeń; szkoła; specjalne potrzeby edukacyjne